The Impact of Varying Numbers of Quadrivalent Human Papillomavirus Vaccine Doses on Anogenital Warts in the United States: A Database Study. Issue 3 (July 2018) - Zeybek, Burak; Lin, Yu-Li; Kuo, Yong-Fang; Rodriguez, Ana M.
Abstract : Objective: The aim of the study was to investigate the effects of 3 or less quadrivalent human papillomavirus (HPV) vaccine doses on anogenital warts in both males and females in the United States. Materials and Methods: We conducted a retrospective database study that included males and females aged 9 to 26 years who received varying numbers of vaccine doses between 2006 and 2015. The primary outcome was the incidence of anogenital warts starting 3 months after the last dose of the HPV vaccine. Proportional hazard regression models were used to examine the association between the number of HPV vaccine doses and the incidence of anogenital warts. The Kaplan-Meier method was used to estimate the proportion of subjects. Results: A total of 440, 532 females and 133, 394 males were included in the study. We found a significant 2-way interaction ( p < .0001) between the number of doses and age. For the group between 15 and 19 years of age, the hazard ratio of anogenital warts for the 3-dose vaccine was 0.58 (95% CI = 0.49–0.70), whereas it was 0.65 (95% CI = 0.49–0.85) and 0.67 (95% CI = 0.51–0.89) for the 1- and 2-dose groups, respectively. Conclusions: Our findings showed that 1, 2, and 3 doses of the quadrivalent HPV vaccine were similarly effective against anogenital warts in 15- to 19-year-old adolescents, irrespective of sex. Abstract : Supplemental digital content is available in the text.